Introducing Increasing Returns to Scale and Endogenous Technological Progress in the Structural Dynamic Economic Model SDEM-2 - Kovalevsky, Dmitry V. (Discontinuity, Nonlinearity, and Complexity, 2026)
Two nonlinear modifications of the Structural Dynamic Economic Model SDEM-2 are developed and studied analytically and numerically. In the first model version described in the present paper the production function is assumed to be nonlinear that leads to increasing returns to scale, while the second model version proposed describes endogenous technological progress by treating the technology parameter of the production function as an additional state variable. Dependent on the values of model parameters and on initial conditions, both modifications of SDEM considered demonstrate two different dynamic regimes: either an explosive economic growth or the collapse of the economy.